2020
DOI: 10.1074/jbc.ra119.012375
|View full text |Cite
|
Sign up to set email alerts
|

The testis-specific LINC component SUN3 is essential for sperm head shaping during mouse spermiogenesis

Abstract: Sperm head shaping is a key event in spermiogenesis and is tightly controlled via the acrosome–manchette network. Linker of nucleoskeleton and cytoskeleton (LINC) complexes consist of Sad1 and UNC84 domain–containing (SUN) and Klarsicht/ANC-1/Syne-1 homology (KASH) domain proteins and form conserved nuclear envelope bridges implicated in transducing mechanical forces from the manchette to sculpt sperm nuclei into a hook-like shape. However, the role of LINC complexes in sperm head shaping is still poorly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…Low sperm count with missing/mislocalized/fragmented acrosome, absence of manchette microtubules Mouse Globozoospermia-like [197] Sad1 and UNC84 domain containing 4 (SUN4)…”
Section: Human Mousementioning
confidence: 99%
“…Low sperm count with missing/mislocalized/fragmented acrosome, absence of manchette microtubules Mouse Globozoospermia-like [197] Sad1 and UNC84 domain containing 4 (SUN4)…”
Section: Human Mousementioning
confidence: 99%
“…Sperm number, motility, and morphology were analyzed as previously described. 13,27,28 Hematoxylin and eosin (H&E) staining and periodic acid-Schiff (PAS)-hematoxylin staining were performed as we reported. 13 TUNEL assay was performed on testicular sections according to the manufacturer's instructions provided with in situ Cell Death Detection Kit (Roche).…”
Section: Phenotypic Analyses Of the Mouse Mutantsmentioning
confidence: 99%
“…Regarding SUN3, it has been shown that Sun3 knockout male mice are infertile with a damaged sperm head and tail. In detail, the major abnormalities happen during spermiogenesis, where SPT nuclei fail to elongate due to the absence of cytoskeletal force transduction to NE, fundamental for head elongation [ 142 ]. As a consequence, the animals produce a low concentration of SPZ characterized by abnormal acrosome, low motility, and globozoospermia phenotype.…”
Section: Linc Complex and Male Infertilitymentioning
confidence: 99%
“…Pasch and coauthors demonstrate that SUN3 also participates in the connection of the manchette to NE by the heterotrimeric LINC complex SUN3/SUN4/KASH1 [ 45 ]. Accordingly, Sun3 knockout mice show a reduction of SUN4 levels in association to abnormal manchette formation [ 142 ]. Spermatogenesis of Sun4 knockout male mice normally progresses up to meiosis, but in the spermiogenesis phase, several post-meiotic aspects are compromised, leading to infertility.…”
Section: Linc Complex and Male Infertilitymentioning
confidence: 99%